Identificação molecular (DNA barcode) da ictiofauna marinha da Província Brasileira Tropical - Matias, Gesika Deva de Araújo (2015)
Most of the world's marine fish stocks are "fully exploited" or reached the maximum permissible. A precise identification of species is the first step to prevent illegal trade and overexploitation. DNA barcode is a molecular approach used to identify species and can be useful as a reference to prevent fraud and illegal trade. Our main goal was to generate DNA barcode sequences to characterize the marine fish fauna in Northeastern Brazil, Tropical Brazilian Province to assess whether cryptic diversity occur as well as to serve as a reference to prevent fraud and illegal trade. A fragment of cytochrome c oxidase subunit 1 gene, COI, was amplified and analyzed according to DNA barcode protocol to 79 species, 64 genera, 36 families and 13 orders of fish. Seventy-eight species had intraspecific distances fewer than 2%, and interspecific distances greater than 2% (4.7-39.9%) suggesting that COI was able to correctly discriminate species of marine fish of Northeastern Brazil, Tropical Brazilian Province. These results reinforce that the morphological identification agree with molecular ones exception to Eucinostomus gula that showed genetic divergence of 13.8%. Bayesian inference suggested the need for a systematic review on Encinostomus genus with unstable taxonomy. Among the species collected, one is vulnerable (Lutjanus cyanopterus) and three are near threatened (Albula vulpes, Rhinobatos percellens and Scarus guacamaia) and all of them are generally catch by local fishermen. The correct identification of marine fish species in Tropical Brazilian Province would certainly help in their conservation and contribute to sustainable management of their fishery resources.